The Music of man. - Menuhin, Yehudi, 1916-1999 (Home Vision, 1987)
Between the Great Wars, music absorbed new elements. Jazz swept across the continents with Louis Armstrong and Count Basie while George Gershwin brought it into theaters and concert halls. Also features Aaron Copland, Martha Graham, Kreisler, Toscanini and Stokowski.